Pengaruh Perlakuan Pematahan Dormansi Secara Kimia Terhadap Viabilitas Benih Delima (Punica granatum L.) - Syahri Ramadhani; Haryati Haryati; Jonatan Ginting (Jurnal Agroekoteknologi, 2015)
The objective of the research was to know effect of chemical dormancy breaking treatments on theviability of pomegranate seeds. The research was conducted at the Laboratory of Seed Technology,Faculty of Agriculture, University of North Sumatra, Medan with a height of ± 25 meters above sealevel, in July 2014, using a completely randomized design with 10 level dormancy breakingtreatments (control, seed soaking treatment with H2SO4 (70%, 80%, 90 %), seed soaking treatmentwith KNO3 (0.1%, 0.2%, 0.3%), and seed soaking treatment with HCl (50%, 60%, 70%)).Parameters observed were germination rate (day), normal seedling (%), abnormal seedling (%),seeds that have not grown (%), and vigor index. The results showed that seed soaking treatmentwith H2SO4 significantly affect normal seedling, rate of germination, seeds that have not grown andvigor index but no significant effect on abnormal sprouts.Keyword : pomegranate seeds, dormancy, viability